Optimalisasi Potensi UMKM Melalui Pemanfaatan Media Sosial di Desa Poncorejo Kecamatan Gemuh Kabupaten Kendal - Mafakir; Indriani, Evi; 'Ullalah, Anis; Ismawati, Rekha; Dewi, Kartika Anggie Ismaya; Muzafiroh, Tatkiyatul; Haniesah, Lidiya; Khoiri, Ahmad; Syifa'udin, Abdullah; Sentoso, Ahmad Langga; Munif, Irsa Nur; Haikal, Muhamad Fikri; Fiwaqtilail, Muchammad; Khotimah, Khusnul (Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economy; however, the use of social media as a marketing tool is still not optimal. This study aims to describe the assistance process in utilizing social media for MSME Roti Bolen and Donat Bu Tiyas in Poncorejo Village, Gemuh District, Kendal Regency. The research employed a descriptive qualitative approach with a field study method through interviews, observations, and documentation. Data were analyzed using the Miles and Huberman interactive model. The results show that assistance provided during the Community Service Program (KKN) improved the MSME owner’s understanding of social media management, particularly in creating promotional content and interacting with consumers. Although the increase in sales was not significant, social media utilization proved effective in expanding market reach and enhancing MSMEs competitiveness.